Fluorescence cell imaging and manipulation using conventional halogen lamp microscopy. - Kazuo Yamagata (Public Library of Science (PLoS), 2012)
Technologies for vitally labeling cells with fluorescent dyes have advanced remarkably. However, to excite fluorescent dyes currently requires powerful illumination, which can cause phototoxic damage to the cells and increases the cost of microscopy. We have developed a filter system to excite fluorescent dyes using a conventional transmission microscope equipped with a halogen lamp. This method allows us to observe previously invisible cell organelles, such as the metaphase spindle of oocytes, without causing phototoxicity. Cells remain healthy even after intensive manipulation under fluorescence observation, such as during bovine, porcine and mouse somatic cell cloning using nuclear transfer. This method does not require expensive epifluorescence equipment and so could help to reduce the science gap between developed and developing countries.